The negative predictive value of FDG PET/CT staging in early oropharyngeal squamous cell carcinoma and implications to transoral robotic surgery patient selection. (December 2022) - Tapia, Mario; Manji, Jamil; Dhillon, Kaman; Kleid, Stephen; Flatman, Samuel; Prasad, Jessica; Cardin, Anthony; Fua, Tsien; Rischin, Danny; Dixon, Benjamin; J.R Magarey, Matthew
Highlights: This investigation sought to determine the negative predictive value of FDG PET/CT for cervical lymph node metastases in primary oropharyngeal squamous cell carcinoma. In this multicentre retrospective cohort study that included 88 adults, the negative predictive value of FDG PET/CT in patients with T1-2 OPSCC was 70%. This increased to 79% in cN0 and decreased to 66% when there was a single lymph node, a significant difference. Clinically, this amounted to a change in management in 27.3% of cases after neck dissection pathology review. This meant that more than a quarter of subjects tentatively scheduled for staged sneck dissection, then TORS based on favourable clinical staging, were instead offered non-surgical management following the discovery of occult nodal disease on neck dissection pathology. FDG PET/CT can be a reliable tool for assessing the suitability of candidates for single modality TORS, particularly in cases with clinical negative necks. However, the limitations of currently available imaging should be considered when determining management. Abstract: Objectives: Our objective was to determine the negative predictive value (NPV) of preoperative FDG PET/CT for detecting locoregional nodal disease. The aim was to help inform the decision-making process when identifying patients with early-stage OPSCC that would be suitable for transoral robotic surgery (TORS) as a single-modality treatment. Materials and methods: A retrospective cohort study was conducted of adults with primary stage cT1-2 OPSCC with up to one metastatic neck lymph node (cN0-1) planned for TORS. Patients with a preoperative PET/CT and who had undergone staging neck dissection (ND) were included. Clinical and pathological nodal staging was established based on PET/CT and ND, respectively. The primary outcome was the frequency of occult (not seen on PET/CT) nodal disease on ND. Results: Eighty-eight patients were included (N = 88). The rate of occult nodal disease was 28.4 % (n = 25). The NPV of PET/CT in the clinically negative neck was 79 % and 66 % in cases with a single clinical node. Following staging ND, the treatment plan changed in 27 % of cases overall, 7 % in cN0 and 36.7 % in cN1. Among these, 18 % met criteria for radiotherapy and 9 % for CRT. This represented a decrease in the number of ideal candidates for TORS as single-modality treatment from 88 to 64 (73 %). Conclusions: PET/CT is a useful tool in the workup of patients for primary TORS. However, about one third of patients with early-stage OPSCC might benefit from adjuvant therapy not predicted by preoperative PET/CT. A staging ND helps confirm candidates for single-modality treatment with TORS.